(untitled) (Research, Society and Development, 2021)
The objective was to evaluate the potential of using Euterpe precatoria Mart seed to feed pigs. Diets were prepared with different levels of inclusion of açaí seed (0; 7.5; 15 and 22.5%), resulting from the extraction of the stern. Forty four castrated weighing approximately 15 kg and average 60 days of birth pigs were used, distributed in four groups according to the level of inclusion of açaí kernel. After 56 days of feeding, the pigs’ performance and economic viability were evaluated. There was no significant difference in daily feed intake, final weight, weight gain and feed conversion between groups of treatments to the statistical test. The inclusion of up to 22.5% of açaí kernels in the diet did not result in a statistical difference in the thickness of backfat, percentage of lean meat and carcass yield, however it increased the gross and partial net revenue and the economic viability in the test, demonstrating the potential from açaí seed for the production of slow-growing crossbred pigs in the Amazon region, especially in properties that exploit the sustainable extraction of açaí and that can reduce the impact of the fruit residue on the environment when using this by-product in animal feed. Reducing production costs and allowing the promotion of sustainable development in the Amazon region.